2016
DOI: 10.1037/pag0000081
|View full text |Cite
|
Sign up to set email alerts
|

Multi-domain training enhances attentional control.

Abstract: Multi-domain training potentially increases the likelihood of overlap in processing components with transfer tasks and everyday life, and hence is a promising training approach for older adults. To empirically test this, 84 healthy older adults aged 64 to 75 years were randomly assigned to one of three single-domain training conditions (inhibition, visuomotor function, spatial navigation) or to the simultaneous training of all three cognitive functions (multi-domain training condition). All participants traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 97 publications
(171 reference statements)
0
62
0
9
Order By: Relevance
“…The first group of participants had undergone multi-domain training and the second group of participants had undergone visuomotor function training approximately a year before (the time interval between posttest and EEG session did not differ between groups [ t (27) = −.76, p  > .40]; both groups: M  = 11.7 months, SD  = 0.72, range 11–14 months). Both groups had been randomly assigned to the training groups and practiced the iPad-based Hotel Plastisse training at home during 50 training sessions over 10 weeks [43, 44] (except for one visuomotor participant who had only completed 42 training sessions). Each training session lasted about 45 min and consisted of 5 different training tasks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first group of participants had undergone multi-domain training and the second group of participants had undergone visuomotor function training approximately a year before (the time interval between posttest and EEG session did not differ between groups [ t (27) = −.76, p  > .40]; both groups: M  = 11.7 months, SD  = 0.72, range 11–14 months). Both groups had been randomly assigned to the training groups and practiced the iPad-based Hotel Plastisse training at home during 50 training sessions over 10 weeks [43, 44] (except for one visuomotor participant who had only completed 42 training sessions). Each training session lasted about 45 min and consisted of 5 different training tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Participants in the original training study [44] were contacted by phone and asked whether they were willing to participate in an additional EEG study. The additional control participants were recruited based on the following criteria: age 61–75 years, fluent in German, self-reported right-handedness, neurologically and psychiatrically healthy, no severe manual motor deficiencies.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Lampit et al (2014a) reported transfer gains from a multi-domain training aimed at reasoning, memory, attention and visuo-spatial abilities to a bookkeeping task closely mirroring a real-world work scenario. In direct comparisons to single-domain interventions, multi-domain cognitive training has additionally been associated with more pronounced benefits in far transfer tasks measuring executive attentional control (Binder et al, 2016) and increased longevity of training-related performance benefits (Cheng et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For some cognitive-training programmes, there are not enough studies to perform a proper meta-analysis. Examples include the abovementioned ACTIVE trial, commercial brain-training games (e.g., Neuroracer, Lumosity, and BrainHQ) and multi-domain training programmes (Duyck and Op de Beeck 2019;Buitenweg et al 2017;Binder et al 2016). To date, none of these regimens have shown compelling evidence, or any evidence at all, of training-induced far transfer to either cognitive tests or real-life skills (for a review, see Sala &Simons et al, 2016).…”
Section: Other Cognitive Training Programmesmentioning
confidence: 99%